Estimated Fetal Weight Accuracy in Macrosomic Fetuses Versus Fetuses of Normal Weight [37K]. (May 2018) - Holloman, Conisha; Kostamo, Kathryne; Bahamon, Camila; Mcwhorter, Jeannie; Jodicke, Cristiano; Carlan, Stephen
Abstract : INTRODUCTION: The purpose of this study is to compare the accuracy of estimated fetal weight (EFW) between those fetuses with EFW >90 percentile and those with EFW less than or equal to 90 percentile. METHODS: Retrospective study of all pregnant women from January 2010 to September 2013 who had an ultrasound (US) and delivered within a week. Group 1=EFW >90 percentile for gestational age. Group 2=EFW <or equal to 90 percentile. Primary outcome included birth weight (BW) at delivery. Secondary outcomes included cesarean section (CS) and induction rate. Statistical analysis included χ 2 and student t -test for categorical and continuous variables, respectively. RESULTS: Group 1=133 cases and Group 2=930 cases. There were no significant differences in age, race/ethnicity and gravidity status between the two groups. Class II (23% versus 14%) and III (26% versus 16%) obesity, EGA at scan (39.0±1.5 versus 38.3±2.0 weeks) and delivery (39.3±1.5 versus 38.0±1.9 weeks), CS rate (65% versus 41%), EFW by US (4, 042±330 versus 3, 057±518 g), birth weight (3, 848±404 versus 2, 972±517 g) and weight difference (−194±302 versus −85±241 g) were noted to be higher in group 1 ( P <.05). Induction of labor rate (23% versus 32%) was higher in group 2. CONCLUSION: The accuracy of US generated EFW is an important factor in determining route of delivery. Our data suggests that the larger the EFW by US the greater the chance of error when compared to the BW of smaller infants.